How Often Excitation Precipitates Seizure? Relative Difference of Frequency and Significance in Different Types of Epilepsy (Journal of Medicine, 2012)
Background: Epilepsy is a chronic neurological disorder, which presents with recurrent, unprovoked seizures. Seizure occurs spontaneously usually, but there may be association of various triggers. These triggers may act as seizure precipitating factors (SPFs). Objective: To find out the frequency of excitation as a SPF and its relationship to different types of epileptic patients attending Neurology and Medicine outpatient department (OPD) of a tertiary care hospital in Bangladesh. Methods: This was a cross sectional study carried out in specialized epilepsy weekly outdoor clinic of Neurology and Medicine outpatient department (OPD) of Dhaka Medical College Hospital from January 2008 to July 2011. Epilepsy syndromes were broadly classified into four categories using the classification system of International League Against Epilepsy (ILAE) namely, generalized epilepsy (GE), localization related epilepsy (LRE), symptomatic and unclassified. Each patient was evaluated and classified by consultant neurologist. All participants were interviewed through a predesigned close ended questionnaire to identify frequency of excitation as a SPF. Result: Among all the patients 71.5% were male, with most common age group at the time of interview was 11-20 years (36.8%). About 62% could identify at least one precipitator. Excitation (25.2%) was the most common SPF reported by patients followed by emotional stress in 17.7%. Excitation was found to be significantly associated with generalized epilepsy (p